Mental‐health‐related stigma among Japanese children and their parents and impact of renaming of schizophrenia. Issue 3 (7th September 2016) - Koike, Shinsuke; Yamaguchi, Sosei; Ohta, Kazusa; Ojio, Yasutaka; Watanabe, Kei‐ichiro; Ando, Shuntaro
Abstract : Aim: Mental‐health‐related stigma affects help‐seeking behavior and service utilization among young people. Whether mental‐health‐related stigma is different or correlated between parents and their children is unknown. It is also unknown whether the name change of schizophrenia in 2002 has had long‐term effects on reducing stigma for adults in the general population. Methods: We recruited 143 parent–child pairs (mean ages [SD]: 51.5 [3.6] and 21.2 [1.2] years, respectively) to complete self‐report questionnaires regarding mental‐health‐related stigma and experience. We also assessed negative stereotypes for three psychiatric disease names (old and new names of schizophrenia, and depression), and for diabetes mellitus as a physical illness comparison. The questionnaires also asked respondents to identify the old and new names of schizophrenia and dementia, respectively, among 10 names for mental and physical illnesses and conditions. Results: Parents showed lower stigma levels toward mental illness and diabetes mellitus, but similar or greater stigma levels toward schizophrenia, compared with their children. Stigma levels toward mental illness in parents and their children were significantly correlated. The rate of correct identification of the old and new names for schizophrenia was higher in parents than in their children (64.7% vs 41.4%, P < 0.001). Parents who responded correctly endorsed more negative stereotypes toward the new name of schizophrenia compared with those who responded incorrectly ( P = 0.049). Conclusion: The present findings suggest that stigma toward mental illness is shared between family members, and the name change of schizophrenia has effectively reduced stigma levels toward this disorder in adults of various ages.